HARNESSING THE POWER OF SERVICE QUALITY TO ATTRACT AND RETAIN STUDENTS: AN OUM EXPERIENCE - Kamariah Mohd Noor,; Mohamad Afzhan Khan Mohamad Khalil,; Latifah Abdol Latif, (2016)
The increase in the number of open and distance learning (ODL) providers in Malaysia has provided potential students with bigger opportunities to access tertiary education. However, the challenge faced by the providers is that they have to compete with each other to capture the largest number of students. Getting a good intake is a necessity, retaining the existing students is equally critical as these two factors determine the financial sustainability of the institution. As in any service industry, service quality is key to the success of any higher education including ODL institution. Past studies have proposed that satisfaction is one of the key competitive advantages for a HEI as it will lead to profitability and customer loyalty. In this light, this study examines the relationship between service quality and satisfaction of Open University Malaysia (OUM) students. A performance-based instrument called SERVPERF developed by Cronin and Taylor (1992) was used as a guide for this study, some modifications were made to suit the context of OUM. The instrument consists of two sections, one of which contains 15 demographic questions and the other 65 questions measured on a 5-point Likert-type scale ranging from 1 (strongly disagree) to 5 (strongly agree). Out of 22,000 active students population, 4062 (18.5%) responded and 3290 completed questionnaires were used. Data were analysed using descriptive statistics, correlation and multiple regression. The results indicated that ‘programme’, ‘teaching & learning’, ‘assurance’, ‘responsiveness’, ‘empathy’ and ‘reliability’ explained 77.9% of the variation in student satisfaction. ‘Empathy’ and ‘responsiveness’ have the greatest impact on satisfaction in the students’ perception of service quality rendered by OUM. The overall satisfaction level measured falls at 77.0% with a mean score of 3.85 on a 5 point Likert scale.